2020
DOI: 10.1111/ejh.13466
|View full text |Cite
|
Sign up to set email alerts
|

High levels of immunoglobulin expression predict shorter overall survival in patients with acute myeloid leukemia

Abstract: Objectives It has been believed that immunoglobulins can only be produced by B lymphocytes and plasma cells. We have previously reported that IgG can be expressed in myeloblasts from patients with acute myeloid leukemia (AML) and plays a role in the proliferation and apoptosis of leukemic cells. However, its clinical impact has not been assessed. Methods We assessed the expression of different classes of immunoglobulin in peripheral blood and bone marrow samples from 132 AML patients and correlated the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We have detected Igs on the cell surfaces of myeloblasts by multicolor flow cytometry [ 19 ]. High levels of Ig staining signals were associated with poor overall survival.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have detected Igs on the cell surfaces of myeloblasts by multicolor flow cytometry [ 19 ]. High levels of Ig staining signals were associated with poor overall survival.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that detection of a high level of IgG on AML blasts by flow cytometry analysis, coupled with Igκ or Igλ, is associated with poor overall survival [ 19 ]. Considering that AML-derived Ig could not only be on the cell membrane, but may also be located in the cytoplasm or secreted into the circulation, we further assessed AML-derived Ig expression in sorted myeloblasts by qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA extracted from BM was amplified and subjected to mutation analysis using a panel of 28 ( n = 12 cases) or 81 ( n = 32 cases) genes (commonly mutated in hematopoietic neoplasms) by NGS on an Illumina MiSeq platform (Illumina Inc., San Diego, CA, USA), as described previously [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of cancer-derived Ig in sarcomas was confirmed in the sarcoma cell lines A673, U-2 OS and HT1080 ( 38 ). In addition, cancer-derived Ig is frequently expressed in acute myeloid leukemia cells ( 39 42 ). Thus, cancer-derived Ig is validated to be widely expressed in different cancer lineages, including epithelial cancers, soft tissue tumors, and hematopoietic neoplasms.…”
Section: Wide Expression Of Ig In Cancer Cellsmentioning
confidence: 99%